‘Sorrento’ and ‘Tulare’ Walnut Cultivars: Morphological Traits and Phytochemical Enhancement of Their Shell Waste - Elvira Ferrara; Danilo Cice; Simona Piccolella; Assunta Esposito; Milena Petriccione; Severina Pacifico (Molecules, 2024)
Walnut processing generates considerable quantities of by-products that could be reprocessed into value-added products that have food and non-food applications. In this context, the aim of this study is to characterize the ‘Sorrento’ and ‘Tulare’ walnut cultivars using the UPOV guidelines and analyze the chemical composition and antioxidant activity of their shells. Insight into the chemical composition of the different granulometric fractions of walnut shell, obtained by sieving, was obtained following ultrasound-assisted extraction by Ultra-High-Performance Liquid Chromatography–High-Resolution Mass Spectrometry (UHPLC-HRMS). The total phenolic, flavonoid, and tannin content and antiradical capacity, obtained by DPPH and ABTS assays, and the Fe(III) reducing power of the extracts were also evaluated. The UHPLC-HRMS analysis indicated the presence of thirty-two compounds ascribable to four major classes of specialized metabolites. Furthermore, the extraction efficiency of gallic acid, ellagic acid derivatives, as well as glansreginin A, increased with the decrease in shell matrix particle size in contrast to chlorogenic acids and flavonoid glycosides. This is the first study to highlight new knowledge on the chemical composition of walnut shells. The results obtained demonstrate the feasibility of recovering valuable bioactive components from agro-waste that may be further valorized.